Efficacy and safety of over-the-scope clips for colorectal leaks and fistulas: a pooled analysis. Issue 6 (1st August 2022) - Wang, Qianyu; Li, Jie; Liu, Shuang; Fang, Changzhong; Chen, Wenliang
Abstract: The development of laparoscopic technologies and continuous improvements in intracavitary anastomosis technology have significantly reduced the incidence of anastomotic leak (AL) following colorectal surgery. However, AL incidence can significantly increase the duration of patient hospitalization, patient medical expenses, and incidence of mortality. The recently developed over-the-scope clip (OTSC) system has been of increasing clinical interest owing to its ease of use, low complication rates, and high rates of technical and clinical success. The PubMed/Medline, EMBASE, and Cochrane PubMed Library were systematically searched for all studies of OTSC system-mediated closure of ALs and fistulas published from January 2010 to January 2021. Two reviewers independently identified relevant studies based on appropriate inclusion and exclusion criteria. A total of nine studies were included in the present analysis, incorporating 114 patients of whom 107 were treated with an OTSC system. The technical success rate for these patients was 84% (95%CI, 73.5–94.5%; I 2 53%), and the clinical success rate was 74.3% (95%CI, 64.4–84.1%; I 2 28%) as calculated via a pooled proportion analysis. Complications occurred in two patients. The endoscopic OTSC system is a safe and effective means of treating ALs and fistulas after colorectal surgery.